1988
DOI: 10.1152/ajpheart.1988.254.5.h919
|View full text |Cite
|
Sign up to set email alerts
|

Response of arteriolar network of skeletal muscle to sympathetic nerve stimulation

Abstract: The influence of vessel location on arteriolar responses to sympathetic nerve stimulation was systematically studied in a skeletal muscle arteriolar network under normal and altered tissue O2 levels. The exteriorized cat sartorius muscle was exposed to 0, 5, and 10% ambient O2 during sympathetic chain stimulation at 8 pulses/s. Under 0% O2, stimulation initially caused a 25-45% constriction that was faster and more pronounced in distal arterioles. Ninety-one percent of vessels showed a secondary dilation (symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 0 publications
3
42
1
Order By: Relevance
“…In resting muscles, sympathetic nerve stimulation constricts all resistance vessels. Increasing the stimulus frequency of SNA from 0.5 Hz through 16 Hz produces a full range of vasoconstriction mediated primarily through the release of norepinephrine (5,21,50,60,95). However, there is a rank order of responsiveness to SNA that varies with location in the resistance network.…”
Section: Sympathetic Innervation Of Skeletal Muscle Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…In resting muscles, sympathetic nerve stimulation constricts all resistance vessels. Increasing the stimulus frequency of SNA from 0.5 Hz through 16 Hz produces a full range of vasoconstriction mediated primarily through the release of norepinephrine (5,21,50,60,95). However, there is a rank order of responsiveness to SNA that varies with location in the resistance network.…”
Section: Sympathetic Innervation Of Skeletal Muscle Vasculaturementioning
confidence: 99%
“…When SNA is sustained (2-3 min) in resting muscle, distal arterioles have a tendency to "escape" from sympathetic vasoconstriction and exhibit a secondary relaxation (5,27,60). In contrast, vasoconstriction is sustained in proximal arterioles and feed arteries (50,95).…”
Section: Sympathetic Escape In Resting Muscle and The Distribution Ofmentioning
confidence: 99%
“…This could arise from preferential activation of small resistance vessels (arterioles) that possess a2-adrenoceptors2,13,14 at low-frequency nerve stimulation. It is well known that an inverse relation exists for resistance vessel diameter and sensitivity to SNS and catecholamines.213, [15][16][17][18][19][20][21][22][23] At the microvascular level, previous studies of skeletal muscle indicate that smooth muscle of large arterioles and muscular venules possess both types of a-adrenoceptors and that small terminal arterioles have predominantly a2-adrenoceptors.2,13,14 Other studies indicate that both arteriolar levels are densely innervated in skeletal muscle, with sparse or no innervation of muscular venules. [16][17][18]24 It is possible that low-frequency nerve stimulation constricts predominantly small arterioles with a large dependence on a2-adrenoceptors.…”
Section: Ohyanagi Et Al Sympathetic Nerve Stimulation Of Microvasculamentioning
confidence: 99%
“…Previous studies in intact animals and humans have suggested that sympathetic vasoconstriction in contracting muscle is both ( a ) well preserved (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), thereby partially offsetting metabolic vasodilation to maintain blood pressure (29); and ( b ) largely negated by metabolic vasodilation (30)(31)(32)(33)(34)(35)(36)(37)(38), thereby optimizing muscle perfusion. The latter concept, initially termed "functional sympatholysis" (30) recently has been extended by reductionist microcirculatory preparations (39)(40)(41)(42)(43)(44)(45) demonstrating that certain local metabolic consequences of contraction (e.g., intramuscular acidosis, hypoxia) interfere with specific signal transduction pathways mediating alpha-adrenergic vasoconstriction. Furthermore, the alpha adrenergic receptors that are most susceptible to such metabolic inhibition are those located on the distal nutrient arterioles, which are most accessible to metabolic products of contraction; in contrast, adrenergic receptors located on more proximal resistance arteries are not so accessible to these metabolic products (42).…”
Section: Introductionmentioning
confidence: 99%